(6m-3)+m-4=0

Simple and best practice solution for (6m-3)+m-4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6m-3)+m-4=0 equation:


Simplifying
(6m + -3) + m + -4 = 0

Reorder the terms:
(-3 + 6m) + m + -4 = 0

Remove parenthesis around (-3 + 6m)
-3 + 6m + m + -4 = 0

Reorder the terms:
-3 + -4 + 6m + m = 0

Combine like terms: -3 + -4 = -7
-7 + 6m + m = 0

Combine like terms: 6m + m = 7m
-7 + 7m = 0

Solving
-7 + 7m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 7m = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 7m = 0 + 7
7m = 0 + 7

Combine like terms: 0 + 7 = 7
7m = 7

Divide each side by '7'.
m = 1

Simplifying
m = 1

See similar equations:

| 55n+210= | | 11.95+1.71= | | 0.7x+0.8=5.7 | | 6/1/5=1/4/m | | f(x)=0.5-2x+5 | | 8x+1=2x+40 | | x+(x*.15)=30 | | x+(x*.15)=25 | | 6(1+2x)=5(3-x)+25 | | 6x^2-18x-12=0 | | 7x+12=3(2x+9) | | x/4y=19 | | 2x^2+mx+9=0 | | 6x+8x=12 | | t=144.67+0.39m | | [x-4]=6x+16 | | (1/7÷4/5)×7/9 | | g-8=-2 | | 2e^3x-1=9 | | 8/7m-36/7=12 | | 8/7m-36=12 | | X^2+4x-360=0 | | 23/x=23/4/5 | | 15y-10y=15 | | (x+5)+(2x+25)=90 | | ((z-4)/6)-2=(z/2) | | 5/3-3/4 | | (-9x)-22=(-3x)-4 | | 1/4(8x-12) | | (9x)-22=(-3x)-4 | | 32/0.2 | | (x+5)+(2x+5)=90 |

Equations solver categories